BANK DIGITAL DAN KEPERCAYAAN KONSUMEN - Sudung Simatupang; Onita Sari Sinaga; Sepbeariska Manurung; Marthin Hutler Ambarita; Erna Ningsih Mokodongan (Jurnal Ilmiah Satyagraha, 2024)
Abstract –Transformation in the banking world has changed the form of bank work processes, from conventional bank models to digital banks. The purpose of this study is to see an overview of the presence of digital banks through relegation from Bank Indonesia and the Financial Services Authority in the process of trying to gain consumer trust, because consumers still do not fully understand about digital banks and the risks that will be faced when using digital banks because the physical form of the bank cannot be seen by consumers. Digital banks must be able to foster consumer trust through transaction security, accuracy and availability of services, responsiveness to consumer problems, innovation and openness, consumer awareness, and compliance with government regulations and being able to maintain customer privacy and ethics as consumers.